Saturn From Cassini-Huygens 2009
DOI: 10.1007/978-1-4020-9217-6_17
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Evolution of Saturn's Ring System

Abstract: ABSTRACT:The origin and long-term evolution of Saturn's rings is still an unsolved problem in modern planetary science. In this chapter we review the current state of our knowledge on this longstanding question for the main rings (A, Cassini Division, B, C), the F Ring, and the diffuse rings (E and G). During the Voyager era, models of evolutionary processes affecting the rings on long time scales (erosion, viscous spreading, accretion, ballistic transport, etc.) had suggested that Saturn's rings are not older… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 187 publications
3
63
0
Order By: Relevance
“…The Voyager-era (1980s) perspective was that today's planetary ring systems cannot be primordial but must be continuously regenerated from their local arrays of moonlets, through vigorous evolutionary processes (3,4). To create Uranus' narrow rings, or the diffuse rings of Jupiter or Neptune, merely requires destroying a 1-to 10-km-diameter moonlet by impact with a heliocentric interloper.…”
mentioning
confidence: 99%
“…The Voyager-era (1980s) perspective was that today's planetary ring systems cannot be primordial but must be continuously regenerated from their local arrays of moonlets, through vigorous evolutionary processes (3,4). To create Uranus' narrow rings, or the diffuse rings of Jupiter or Neptune, merely requires destroying a 1-to 10-km-diameter moonlet by impact with a heliocentric interloper.…”
mentioning
confidence: 99%
“…In contrast, prior ring origin models produce an initial ring comparable in mass to the current rings (Charnoz et al, 2009;Dones, 1991). Salmon et al (2010) found that such dense rings can evolve to something resembling Saturn's ring by viscous spreading after O(10 8 ) years, but it is not clear how the ignored MMRs with the closest satellites such as Mimas would affect this evolution.…”
Section: Mass (Planetary Masses)mentioning
confidence: 84%
“…Here, the stripped material accumulates in a pure ice moon whose final mass is m o 10 25 g. Canup estimated that the location of synchronous orbit around a newly formed Saturn would be located at about 3R S due to the slower rotation of the more distended planet, so that this ice moon eventually spirals inward due to planetary tides, but at a slower rate than the original satellite due to its smaller mass. For planetary tidal parameters (k 2 /Q) P (with likely values 10 À6 k 2 /Q P 10 À5 ; e.g., Charnoz et al, 2009), the ice moon takes $10 6 years [5 Â 10 À6 /(k 2 /Q) P ] [10 25 g/m o ] to decay within the ice Roche limit, where it disrupts into a massive ice ring. This timescale is long enough that the ring forms after the remnant satellite has collided with Saturn and when the circumplanetary gas disk has essentially dissipated.…”
Section: Mass (Planetary Masses)mentioning
confidence: 99%
“…Values of Q as high as 10 7 have been proposed for stars (Penev et al 2012), and this value could lead to τ ∼ 10 8 yr if we assume k 2 ∼ 0.1, as expected for giant planets (Yoder 1995). Ring systems are believed to have several possible origins: the result of impact events (e.g., Tiscareno 2013), captured objects or satellites that are tidally destroyed (e.g., Charnoz et al 2009b;Canup 2010), or even remnants from planet formation (though this last hypothesis is less likely - Charnoz et al 2009a). In all cases, they settle in a special plane around the planet, called the Laplacian plane (e.g., Lehébel & Tiscareno 2015).…”
Section: Tilted Rings?mentioning
confidence: 99%